Implementasi Akad Mudharabah Pada Produk Asuransi Syariah di Indonesia - Nur Widya Ningsih; Zainarti Zainarti (Pusat Riset dan Inovasi Nasional, 2025)
Mudharabah contracts are used in Indonesian sharia insurance products to provide financial solutions that comply with Islamic sharia rules. According to the terms of the contract, insurance companies act as fund managers (mudharib) and participants as capital owners (shahibul mal), working together to share profits. This study used a qualitative descriptive method to assess the concept, implementation mechanism, and implementation obstacles. The study’s findings show how the mudharabah contract promotes socioeconomic sustainability by prioritizing justice, openness, and trust; however, more attention is required to issues such as competition from conventional insurance and a lack of Islamic financial knowledge.